Analisis Tingkat Stress Dan Kecemasan Atlet Pencak Silat Pada Fase Pra-Kompetisi Pendekar Cup PSPS Bakti Negara Ke-XXIII Tahun 2025 Di Kota Denpasar - Siti Khotijah Rahma; I Ketut Yoda; Luh Putu Tuti Ariani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study is to determine the levels and triggering factors of stress and anxiety among pencak silat athletes during the pre-competition phase of the Pendekar Cup PSPS Bakti Negara XXIII in Denpasar City in 2025. The research method employed is a quantitative descriptive approach involving 40 athletes selected through purposive sampling based on predetermined criteria. The instruments used in this study were the Perceived Stress Scale (PSS) to measure stress levels and the Sport Anxiety Scale-2 (SAS-2) to assess anxiety. The results indicate that most athletes fall into the moderate category for both stress and anxiety. This finding shows that the pre-competition phase is a period highly susceptible to psychological pressure, including mental, physical, and social aspects, which may affect athletes’ performance. In conclusion, pencak silat athletes in the pre-competition phase tend to experience moderate levels of stress and anxiety; therefore, systematic mental management is necessary to maintain psychological stability and optimize performance during competition. Keywords: Anxiety, Pencak Silat, Stress